Combining sensory panels with Analytic Hierarchy Process (AHP) to assess nectarine and peach quality - Amparo Baviera-Puig; Mónica García-Melón; Isabel López-Cortés; María Dolores Ortolá (Cogent Food & Agriculture, 2023)
AbstractThe aim of this study is to combine the Analytic Hierarchy Process (AHP) with sensory analysis for assessing the quality of stone fruits, such as peaches and nectarines. To this end, a multicriteria model based on the AHP is proposed, which could be used in any process of evaluation or selection of these fruits. It is compared with the Quantitative Descriptive Analysis (QDA) performed by trained panellists. The AHP results showed that gustatory phase was the most important attribute in both the positive (54%) and negative (80%) models. In the next level of attributes, the most important were sweetness and juiciness (63.1% of the weight for nectarines and 55.1% for peaches), while for rejection the most important attributes were the bitter, sour or astringent sensation of the gustatory phase (around 25% each attribute). The prioritisation obtained for the samples of fruits was the same as the QDA. AHP also provided the tasting profile of every panellist. With the AHP, time and costs are saved and accuracy of the results is improved. In the case of stone fruits, where variability is high throughout the season, the combination of QDA and AHP can help the food industry by matching consumer’s expectations better and faster.